PENGURANGAN PARAMETER KAWASAN PERMUKIMAN KU-MUH DI SINDUADI SLEMAN BERDASARKAN PERMEN PUPR 02/2016 - Nurokhman, Nurokhman (Jurnal Teknik Sipil, 2019)
Sinduadi urban settlements with rapid population growth as a result of the growth of property, shopping, industry, campus and tourism businesses have the potential to create slum areas. Based on the 2016 Sleman Regent Decree in RT 011 RW 026 Kutu Dukuh have an area of 1.23 hectares of slums. To decrease size of slum areas, it is necessary to study calculations in accordance with applicable regulations. The purpose of the study was to identify the parameters determining the slum, calculate slum scores, reduction in slum area and slum level at the end of 2018. Data were taken from survey results and the Sleman KOTAKU Program document. From the analysis of slum measurements with 19 parameters the value is 23 (light slum category) measured based on PUPR Regulation No. 2/2016 which uses 7 aspects and 19 parameters, such as the limitations of building conditions, roads, clean water, waste management, drainage and the unavailability of hydrants. The initial calculation results show a score of 23 consisting of the unavailability of drainage value of 3, a waste management system that does not conform to the technical standard of value 5, the non-maintenance of waste management facilities and infrastructure of value 5, and the unavailability of a fire protection facility of value 5. For handling investment is required in the form of paving roads ( 853.5 m2), rainwater infiltration wells (18 units), drainage channels (154.5 m1), public hydrants (HU) clean water (10 units) and 3R waste (39 kk) which become the final score of 14 (< score 19) which means not slum.